Start up business solution using machine learning - Sohan, Saad Ahmed; Nakib, Ayman; Ahmed, Tanvir (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.